Chemical analysis, biological and therapeutic activities of Olea europaea L. extracts. Issue 11 (2nd June 2022) - Alesci, Alessio; Miller, Anthea; Tardugno, Roberta; Pergolizzi, Simona
Abstract: The Olea europaea L. is a very well-known and widely used plant, especially for its nutritional qualities. Its extracts from leaves and fruits are widely used in contrasting and preventing various pathologies. In this review, the collected data highlight important chemical analyses and biological effects of this plant extracts. It exhibits cholesterol-lowering, hypoglycemic, cytotoxic, antibacterial, neuroprotective, antioxidant, anti-inflammatory and hypotensive activities. The results show that extracts from O. europaea could be used as a food additive in the supplementary treatment of many diseases. Graphical Abstract: UF0001